Atención al cliente en la empresa bar fénix en la ciudad de ventanas en el periodo 2022 - Pérez Rivera, Christian Eduardo (2023)
The implementation of this case study is based on customer service in the Bar Fénix company in the city of windows in the period 2022, which has investigative objectivity focused on analyzing the process reflected in serving users to improve the service provided by the company, this allows us to identify the methods related to this topic that should be used by observing how employees treat consumers to provide a better service and purchasing experience, considering that the possibility of achieving what is established It is through the use of effective tools such as surveys aimed at this type of people who consume the different products that the business sells, since, in this way, the internal problems that are affected by these types of procedures will be identified. Therefore, the objective of the work is based on the analysis of the customer service process, by obtaining information through primary and secondary sources, to improve the service provided by the company. Therefore, it is considered that through this collection of information it will be possible to determine the factors that generate problems in the sales service that are applied in Bar Fénix, where investigative techniques such as interviews with the administrator and surveys of consumers of the business have been the very important key to achieving and fulfilling the objectivity of this analytical report.